Spirituality, Evolution, Creator God. (June 2018) - Haight, Roger
Evolution raises problems for some Christian beliefs, such as the character of God's creating act, whether God intervenes in nature's consistency, God's purpose in the light of nature's randomness, and whether we can refer to anything specific God does in history. This article addresses these issues first with some abstract conceptions of God, and then with considerations of the nature of God creating, the immanence and transcendence of God, and God's "action" in the world. It concludes with reflections on the Christian life in the light of this theological construction.